Frequency of TERT Promoter Mutations in Prostate Cancer - Stoehr, Robert; Taubert, Helge; Zinnall, Ulrike; Giedl, Josef; Gaisa, Nadine T.; Burger, Maximilian; Ruemmele, Petra; Hurst, Carolyn D.; Knowles, Margaret A.; Wullich, Bernd; Hartmann, Arndt (Pathobiology, 2015)
Recently, recurrent mutations within the core promoter of the human telomerase reverse transcriptase (TERT) gene generating consensus binding sites for ETS transcription factor family members were described in melanomas and other malignancies (e.g. bladder cancer, hepatocellular carcinoma). These mutations were discussed as early drivers for malignant transformation. In prostate cancer (PrCa) TERT expression has been associated with a poor prognosis and higher risk for disease recurrence. The underlying mechanisms for high TERT expression in PrCa have still not been clarified. To date, data on TERT promoter mutation analysis in PrCa are sparse. Therefore, we performed sequence analysis of the core promoter region of the TERT gene in an unselected cohort of prostate tumors.Sections from 167 formalin-fixed, paraffin-embedded and cryopreserved prostate tumors were microdissected and used for DNA isolation. The mutation hotspot region within the TERT core promoter (-260 to +60) was analyzed by direct Sanger sequencing or SNaPshot analysis.All cases were analyzed successfully. Mutations within the core promoter of the TERT gene were not detected in any of the cases with all tumors exhibiting a wild-type sequence.TERT core promoter mutations reported from several other malignancies were not detected in our unselected cohort of PrCa. These data indicate that alterations within the core promoter of the TERT gene do not play an important role in prostate carcinogenesis. © 2015 S. Karger AG, Basel.
EVALuna2:6706